DETERMINANTS OF INTRA-ASEAN FDI: EVIDENCE FROM THE PANEL DATA ANALYSIS - Dr. Neha, Dr. Shilpa Garg (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Purpose: Since FDI has become more significant, so has the literature on FDI; as a result, numerous studies have examined the factors that influence FDI inflows. However, there needs to be more literature on the determinants of Intra-ASEAN FDI. This research attempt to determine the effect of economic, social, institutional, natural resources, and time- invariant variables on intra –ASEAN FDI inflows. Design/methodology/approach:This study includes a data set from 2001 to 2019. The Driscoll-Kraay standard error approach was employed to investigate the influence of significant drivers of intra-ASEAN FDI through random effect, given the presence of cross-sectional dependency, autocorrelation, and heteroscedasticity among the cross-sectional units. Findings:It was found that GDP, distance, labour, common border, and common effective preferential tariff were essential determinants of intra-ASEAN FDI. Originality:This research adds to the existing literature in the following ways: firstly, we tried to incorporate more categories of variables instead of taking one or two categories of variables. We have covered the bilateral studies' economic, social, institutional, natural resources, and time-invariant variables to determine the determinants of intra- ASEAN FDI. Secondly, the current study has checked the cross-sectional independence among the cross-sectional units, which previous scholars still need to check. So the methodology used by the current studies is also contributing to getting better results for intra –ASEAN FDI.